Beneficial body mass index to enhance survival outcomes in patients with early-stage hepatocellular carcinoma following microwave ablation treatment - Jian-Ping Dou (International Journal of Hyperthermia, 2020)
Purpose To identify the beneficial body mass index (BMI) for patients with hepatocellular carcinoma (HCC) to achieve longer survival time following curative microwave ablation (MWA). Methods This retrospective study evaluated 474 patients with solitary primary HCC who underwent MWA. BMI at initial admission and other characteristics were collected. The associations of the BMI with the overall survival (OS) and disease-free survival (DFS) were analyzed by Cox proportional hazards regression analysis in multiple models. A two-piecewise linear regression model was applied to examine the threshold effect of the BMI on OS and DFS by maximized log likelihood method. The threshold level was determined by using trial and error. Results Patients with a normal BMI range achieved improved survival outcomes but similar DFS in multiple models. In the model with adjustments of the age, size, and Charlson score, patients with BMI ≤ 22.9 and ≤24.9 kg/m2 exhibited a lower death rate than patients with BMI ≤18.5 kg/m2 (p < 0.05). U-shaped relationships between the BMI and OS were illustrated when the BMI was set as a continuous variable. The death prevalence decreased with an increasing BMI up to the first turning point of 21.5 and increased with an increasing BMI up to the second turning point of 23.1 (p = 0.00). The threshold effect analysis indicated that no turning point was selected in the DFS results (p = 0.10). Conclusions The beneficial BMI level for HCC patients following MWA, with a more likely favorable survival outcome, is 21.5 to 23.1 kg/m2.